Faktor Risiko Stunting Dilihat dari ASI Eksklusif dan Hygiene Sanitasi Keluarga pada Anak Usia 6-36 Bulan di Wilayah Kerja Puskesmas Sidoarjo - Rafi' Kunti Imamaturrodiyah; Sri Sumarmi (Universitas Airlangga, 2023)
Background: Growth in children is an indicator to see the health status of children in the future and nutritional status of children. In the growth of the fetus until the age 2 years is a golden period of growth. One of the nutritional problems that many children experience when entering growth is body length or height thait is less than normal or called stunting. Stunting is a chronic malnutrition problem in toddlers which is characterized by low height. Stunting is influenced by various risk factors directly or indirectly. One of the direct risk factors for stunting is history of exclusive breastfeeding and one of the indirect risk factors for stunting is the practice of hygiene and sanitation in the family environment. Objectives: Analyzing the history of exclusive breastfeeding and family sanitation hygiene on the incidence of stunting in children aged 6-36 months in the work area of the Sidoarjo Health Center. Methods: This research is an observational study with a case control approach with a simple random sampling technique which obtained 90 respondents consisting of 45 stunted children and 45 non-stunted children. The research instrument used a questionnaire and microtoise. Results: The results used the chi-square test and odd ratio test. The results of the chi-square test for the history of exclusive breastfeeding were obtained, p=0.000; p<0.05, this explains that there is a significant relationship between a history of exclusive breastfeeding and the incidence of stunting with an OR value of 0.12<1 that exclusive breastfeeding is at risk of 0,12 times experiencing stunting. In addition, the results of the chi-square test on family hygiene and sanitation obtained p value 0.000; p<0.05 which indicates that there is a significant relationship between hygiene and sanitation that is not in accordance with the incidence of stunting and 22.48 times greater risk of experiencing stunting as seen from the results of the OR value. Conclusions: There is a relationship between a history of exclusive breastfeeding and hygiene sanitation in the family environment with the incidence of stunting in children aged 6-36 months in the Sidoarjo Health Center Work Area.